Counseling To Understand And Intervene School Bullying - Haslee Sharil Lim Bin Abdullah; Noor Fadzlina Nawi; Lau Poh Li (Manuscript Central, 2024)
School bullying has been around since time immemorial and has become a pressing issue in schools today. This paper, besides defining and understanding bullying, attempts to help spot the bullies by examining their patterns of behavior and the underlying factors. To alleviate the issue, counseling is proposed as an intervention measure. The paper follows up with a qualitative case study in Malaysia to understand the inner world of a school bully in order to render help services.